The Impact of Visual Art and High Affective Arousal on Heuristic Decision-Making in Consumers - Kim, Yaeri; Park, Kiwan; Kim, Yaeeun; Yang, Wooyun; Han, Donguk; Kim, Wuon-Shik (Frontiers in Psychology, 2020)
In marketing, the use of visual-art-based designs on products or packaging crucially impacts consumers’ decision-making when purchasing. While visual art in product packaging should be designed to induce consumer’s favorable evaluations, it should not evoke excessive affective arousal, because this may lead to the depletion of consumer’s cognitive resources. Thus, consumers may use heuristic decision-making and commit an inadvertent mistake while purchasing. Most existing studies on visual arts in marketing have focused on preference (i.e., affective valence) using subjective evaluations. To address this, we applied a neuroscientific measure, electroencephalography (EEG) to increase experimental validity. Two successive tasks were designed to examine the effects of affective arousal and affective valence, evoked by visual artwork, on the consecutive cognitive decision-making. In Task 1, to evaluate the effect of visual art, EEG of two independent groups of people was measured when they viewed abstract artwork. The abstract art of neoplasticism (AbNP) group (n = 20) was shown Mondrian’s artwork, while the abstract art of expressionism (AbEX) group (n = 18) viewed Kandinsky’s artwork. The neoplasticism movement strove to eliminate emotion in art and expressionism, to express the feelings of the artist. Building on Gallese’s embodied simulation theory, AbNP and AbEX artworks were expected to induce lower and higher affect, respectively. In Task 2, we investigated how the induced affect differentially influenced a succeeding cognitive Stroop task. We anticipated that the AbEX group would deplete more cognitive resources than AbNP group, based on capacity limitation theory. Significantly stronger affect was induced in the AbEX group in Task 1 than in the AbNP group, especially in affective arousal. In Task 2, the AbEX group showed a faster reaction time and higher error rate in the Stroop task. According to our hypotheses, the higher affective arousal state of the AbEX group might deplete more cognitive resources during Task 1 and result in poorer performance in Task 2 because affect impacted their cognitive resources. This is the first study using neuroscientific measures to prove that high affective arousal induced by visual arts on packaging may induce heuristic decision-making in consumers, thereby advancing our understanding of neuromarketing.